1999
DOI: 10.1063/1.370732
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of fluorescent lamp cathode surfaces: BaO/W(001)

Abstract: The BaO/W interaction is responsible for the emission properties of barium–oxide coated tungsten electrode coils in fluorescent lamps. The electronic structure of the BaO/W(001) interface is investigated by first-principles calculations within the local-density approximation of the density functional theory using the full-potential linearized augmented plane wave method. Results are presented for the total density of states (DOS), the atom- and orbital-resolved partial DOS and charge density distributions. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The most important difference is that Ba and BaO are directly adsorbed on a substrate, which is naturally expected to play an active role in the surface interactions. Ab initio calculations, performed by Almanstötter et al [23], for an ordered layer of BaO on W(100), showed significant W-O and W-Ba bonding with strong mixing of the Ba 5d orbitals (unoccupied in the free atom), in addition to the W 5d and O 2p ones. We do not know of any similar calculations for BaO on Ni, but XPS shifts from Ba to BaO on polycrystalline W [27] agree very well with our work down to the monolayer coverage, which was the minimum coverage studied in that work.…”
Section: Correlation Of the Negative Binding Energy Shifts With Publi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The most important difference is that Ba and BaO are directly adsorbed on a substrate, which is naturally expected to play an active role in the surface interactions. Ab initio calculations, performed by Almanstötter et al [23], for an ordered layer of BaO on W(100), showed significant W-O and W-Ba bonding with strong mixing of the Ba 5d orbitals (unoccupied in the free atom), in addition to the W 5d and O 2p ones. We do not know of any similar calculations for BaO on Ni, but XPS shifts from Ba to BaO on polycrystalline W [27] agree very well with our work down to the monolayer coverage, which was the minimum coverage studied in that work.…”
Section: Correlation Of the Negative Binding Energy Shifts With Publi...mentioning
confidence: 99%
“…In order to gain knowledge on the structural, electronic and catalytic properties of AEMO thin films, the atomic and electronic structure should be investigated. Although, over the last decades, a number of studies have been performed related to BaO overlayers on several surfaces, both from the experimental [16][17][18][19][20][21][22] and the theoretical viewpoint [23][24][25], there are still obscure and controversial points concerning how the oxidation of the alkaline earth metal starts and develops on the surface. Among these points are the unusual negative binding energy shifts (NBESs) of some low core atomic levels (Ba 4d and 5p) after barium oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…the extent of covalent bonding between the metal and oxygen). Recently, it was found through ab initio calculations that the bonding of BaO on W(100) involves strong hybridization of the W 5d and, intriguingly, the Ba 5d orbitals which are empty in the free atom, thus explaining the large WF decrease [11].…”
Section: Introductionmentioning
confidence: 99%
“…Electrodes of the fluorescent lamps are usually coated with the barium oxide to improve the release of electrons. 5 The refractive index and luster of the glass can be amplified with the use of barium carbonate. 6 Barium carbonate is also valuable for the decrease in the Xray leaks associated with the cathode ray tubes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the usage mentioned above, the various compounds of Ba can be expended in several applications. Electrodes of the fluorescent lamps are usually coated with the barium oxide to improve the release of electrons 5 . The refractive index and luster of the glass can be amplified with the use of barium carbonate 6 .…”
Section: Introductionmentioning
confidence: 99%